Entry Regulations and Product Variety in Retail - Florín G. Maican; Matilda Orth (Research Institute of Industrial Economics (IFN), 2021)
This paper estimates a dynamic model of store adjustments in product variety that considers multiproduct service technology to evaluate the impact of entry regulations on variety and long-run profits in Swedish retail. Using rich data on stores and product categories, we find that more liberal entry regulation increases productivity and decreases the adjustment costs of variety. Counterfactual simulations of modest liberalizations of entry incentivize incumbents to offer more product categories to consumers while increasing efficiency and long-run profits. Regional differences are reduced as consumers and incumbents obtain more benefits in markets with restrictive regulation. Generous liberalizations of entry induce net exit of product categories and harm incumbents in markets with limited demand.
Keywords: L11; L13; L81; 330; Retail markets; Entry regulation; Product variety; Productivity; Competition